(untitled) (Historia, 2021)
The third edition of John Iliffe‟s history of Africa (the first and second editions were published in 1995 and 2007 respectively) has by no means diminished in quality nor in consequence. The key difference between the third edition and the second is the change in the title of the thirteenth chapter and there are also some significant revisions to include analysis on recent socio-economic and political developments on the continent. Otherwise, the structure and depth of the publication remain essentially the same with a few revisions made to incorporate current scholarship. This is a masterful book which qualifies both as an ideal textbook for teaching and as an introductory course in African history, ideally, at the graduate level, and as a general reference work for those who seek to understand the continent‟s very complicated past.